2008
DOI: 10.1007/s00113-008-1407-y
|View full text |Cite
|
Sign up to set email alerts
|

Lokalisation von TGF-β und PDGF und deren Bedeutung für die Pathogenese der Arthrofibrose

Abstract: Arthrofibrosis is a disabling complication after knee trauma and surgery and is characterised clinically by joint stiffness. Due to an immune response, the proliferation of fibroblasts and synthesis of extracellular matrix proteins are increased. The cytokines transforming growth factor beta (TGF-beta) and platelet-derived growth factor (PDGF) are critical players in tissue fibrosis, stimulating cell proliferation and the production of various extracellular matrix proteins. Tissue samples from the infrapatella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 27 publications
0
8
0
2
Order By: Relevance
“…TGF-β1 is widely accepted as a key mediator of fibrosis in multiple organs and has been demonstrated to be elevated in arthrofibrotic tissue 14 . Treatment of infra-patellar fat pad ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TGF-β1 is widely accepted as a key mediator of fibrosis in multiple organs and has been demonstrated to be elevated in arthrofibrotic tissue 14 . Treatment of infra-patellar fat pad ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used the disease classification provided by the World Health Organization (ICD-10, version 2012). While secondary arthrofibrosis and implant malpositioning were excluded by X-ray examination, postoperative complications such as infection or deep vein thrombosis were excluded as described before 4 6 19 . Patients with actual or suspected arthrofibrosis were divided into three groups due to diagnostic confidence: arthrofibrosis score 1 (Afib1): suspected arthrofibrosis based on clinical findings, short Time diagnosis and incomplete differential diagnosis, Afib2: arthrofibrosis based on clinical findings, Afib3: arthrofibrosis based on strong clinical findings as well as histopathological findings reported by an external institution.…”
Section: Methodsmentioning
confidence: 99%
“…Although the predicted incidence of primary arthrofibrosis after knee replacement is 10%, its pathogenesis is mostly unclear and no diagnostic marker has been described 4 . Until today, the diagnosis is based on histopathological findings and clinical symptoms such as loss of motion 5 6 . Treatment of arthrofibrosis is challenging and several therapeutic strategies have been discussed 4 7 .…”
mentioning
confidence: 99%
“…In the pathogenesis of arthrofibrosis, the persistence of physiological inflammation leads to a transdifferentiation of fibroblasts [1, 7, 17, 24, 25], followed by fibrosis of the soft tissue [1, 18, 19, 26]. Within the context of this tissue transformation, further studies have demonstrated HO in arthrofibrosis [1, 16-19].…”
Section: Discussionmentioning
confidence: 99%